Capital formation and production of carbon emissions in low-carbon development - E.S. Siregar; S.U. Sentosa; A. Satrianto (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: This study aims to examine the endogenous variable, low-carbon development, and valuate its influencing factors, given its pivotal role in environmental protection amid climate change concerns and economic growth. Low carbon development is a new platform to maintain economic growth through reducing carbon emissions and reducing the use of natural resources, because it was predicted that reducing emissions will increase economic growth while preventing forest loss, improving air quality and living standards, and reducing mortality rates.METHODS: Utilizing a quantitative method, this study integrates a novel viewpoint by combining low-carbon development with related emission factors. The study utilizes secondary data, specifically time series data spanning 31 years from 1991 to 2021, which were analyzed using regression study methods. The factors being examined include capital formation, deforestation, land transportation, agricultural land, and industrialization.FINDINGS: Findings reveal that low-carbon development in North Sumatra is influenced significantly by capital formation, deforestation, agricultural land, and industrialization, with land transportation showing no substantial impact. Capital formation has a favorable impact on low-carbon development. But, deforestation, land transportation, agricultural land and industrialization have a negative impact on low-carbon development. Together, these determinants account for 77.55 percent of the variance. Capital formation contributes 19.8 percent, deforestation 15.6 percent, agricultural land 19.0 percent, and industrialization 18.9 percent to low-carbon development.CONCLUSION: The hypothesis established in this study is accepted. To foster low-carbon development in North Sumatra, specific attention is required from local governments. Capital formation is vital. Measures include controlling interest rates, supporting businesses, fostering an investment-friendly climate, ensuring security, and integrating environmental sustainability considerations into project implementation to curb carbon emissions. Prevention of deforestation involves tightening land clearance licenses and enhancing institutional quality through environmental protection and property rights legislation. The   government must strive for promoting eco-friendly agricultural practices with mitigated through outreach programs involving experts who educate farmers on minimizing emissions, reducing carbon emissions from pesticide with using biochar sourced from empty palm fruit bunches and also rice straw which is very easy to obtain at a low cost and is environmentally friendly, and emphasizing environmental preservation policies in the industrial sector like industrial transformation efforts with an effective approach to reducing carbon emissions such as restructuring various aspects of industrial activities, including investment, final demand, intensity and production methods. The implementation of tax emissions and strategic interventions increases the likelihood of realizing low-carbon development in North Sumatra, aligning with sustainable development goals.